A dinâmica fluvial do Riacho dos Bosques, Barreirinhas - MA - MACEDO, Larissa Thais dos Santos de (2023)
Natural processes and human actions consistently modify the environment and change the dynamics of watersheds in varying proportions, but always related to a set of factors that act according to the environmental conditions presented. In the Riacho dos Bosques Basin, located in the municipality of Barreirinhas, northeast of the state of Maranhão (about 260 km from the capital, São Luís), fluvial forms can be distinguished, such as abandoned meanders, forming a complex of small lakes, which characterize the lower course of the river, close to the confluence with the Rio Preguiças. The objective of this research is to characterize the fluvial dynamics of the Bosques stream watershed through the analysis of fluvial forms and processes, as well as the urbanization process in the area. The quali-quantitative method guides the research, which presents as methodological procedures the bibliographical survey, the field work and the processing and treatment of images from remote sensors. The results found indicate an accelerated process of urbanization of the upper course, with a gradual increase in occupation in the medium and lower courses in the period between 2005 and 2018. This occupation is carried out in areas that suffer the direct impact of the overflow process of the basin's water bodies during the rainy season, for example, there is a need for bridges that connect the houses to the streets. The river forms found, including lateral bars, islands and abandoned meanders, are related to factors such as tidal advance and sedimentation in the Riacho dos Bosques.